Apostolski vizitator Agostino Valier - pobudnik obnove kompleksa cerkve Sv. Jurija v Piranu. Interpretacija historičnih virov kot izhodišče konservatorskih raziskav - Kovač, Mojca M. (Annales. Series historia et sociologia, 2007)
The article focuses on the review of archival sources, historical representations and interpretation of conservational research during the course of restoration works on the church of St. George and takes into consideration material remains and finds from this monument as a starting point of its presentation. Representation of the Gothic church building in its original state represents a reference point for determination of subsequent changes performed during restoration. The decision to renovate the old Gothic church, which was in ruins, was a demanding and responsible undertaking for the Church and Municipal authorities, because it demanded substantial financial resources. Two basic options emerged: to renovate the existing church or to build a new one. The initiative for the renovation of the minster in Piran was a visitation of the Veronese bishop Agostino Valiero in 1580, ordered by the Pope Gregory XIII. On the basis of the preserved visitation report, we were able to recognize the endeavours and personal engagement of bishop Valier, who took his task as an opportunity to resolve the dilemmas regarding the renovation of the church in Piran. Through his role as a dignitary of the Church he strived to unite Church and Municipal authorities and ensure financial resources while paying regard to expert architect opinions. The visitation report provides detailed description of the original state of the Gothic church and its furnishings and thus represents a remarkable document of great importance for research of architectural history of the church. The final decision to start renovating the church, elaboration of plans and gathering funds were important issues during the entire decade that followed even though the basic guidelines were set in 1580. The renovation of the church was closely associated with the consolidation of the access path and the slope of the hill the church was built on and included thorough changes of the original medieval church structure. The result of renovation works on the church of St. George are two new buildings: the baptistery of St. John the Baptist, erected as a presbyterial part of the church and a separate bell tower. The question remains whether we can consider this renovation as a construction of a new church. It is to be answered by further research of the course of building works.
Keywords: arhivski viri; cerkev sv. Jurija; cerkve; cerkvena arhitektura; konservatorstvo; Piran; varstvo spomenikov